Pengaruh Pemberian Pendidikan Kesehatan dengan Media Kalender “PINTARE” (Pintar Atasi Diare) dalam Meningkatkan Pengetahuan dan Keterampilan Ibu Tentang Tatalaksana Diare Balita Usia 1-4 Tahun (Studi Kasus di Wilayah Posyandu Desa Growong Lor Kecamatan - -, Fahrunnisa (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Central Java is one of the provinces with a toddler diarrhea outbreaks in 2014 with 35 cases, one of them died. Central Java province each year, an average is above 40%. Scope discovery and treatment of diarrhea in Central Java province in 2015 amounted to 57.9%. Pati Regency found the incidence of diarrhea in children under five is high enough. According to the data of Central Java province in 2014 ranked Pati regency had diarrhea for 18 of the 35 counties and cities in Central Java. This study aims to provide health education and increasing knowledge and skills of mothers and children against diarrheal diseases with the media calendar. This research is a Quasi Experiment design with non-equivalent control group design. Samples in this study of 40 people, with 20 as the experimental samples and 20 as a control sample. The analysis is the analysis of univariate and bivariate analysis which using mc-Nemar test and Chi square test. The results showed that; 1) there is a significant difference in the mother's knowledge regarding the treatment of diarrhea among children aged 1-4 years were given health education with the calendar media and without media calendar (p = 0.011, α = 0.05), 2) there is a difference meaningful skills of mothers about the treatment of diarrhea among children aged 1-4 years were given health education with the calendar media and without media calendar (p = 0.010, α = 0.05). Based on these results it can be concluded that health education is effective in increasing knowledge and skills about the treatment of diarrhea mothers of children aged 1-4 years.     Keywords : Health Education, Knowledge, Skills, Diarrhea